Efficacy of low-dose primaquine plus artemether-lumefantrine or dihydroartemisinin-piperaquine for radical cure of Plasmodium vivax in the Solomon Islands: a randomised clinical trial - James, Robert; Obadia, Thomas; Wini, Lyndes; Bobogare, Albino; Charnaud, Sarah; Ruybal-Pesántez, Shazia; Bourke, Caitlin; Munro, Jacob E.; Moore, Brioni R.; Page-Sharp, Madhu; Manning, Laurens; Liligeto, Urijah; et al. (Frontiers in Malaria, 2025)
BackgroundPrimaquine (PQ) remains the only 8-aminoquinoline endorsed by the WHO for treatment of latent Plasmodium vivax liver-stage parasites. PQ is a prodrug, with metabolism and therapeutic activity influenced by inherent human CYP2D6 polymorphisms and by poorly understood interactions with variably co-administered blood schizontocidal therapies. With widespread chloroquine resistance in P. vivax, radical cure now requires use of one of several artemisinin-based combination therapies (ACTs).MethodsFrom September 2017 to February 2019, a randomised clinical trial was conducted in Guadalcanal, Solomon Islands, to evaluate the safety and efficacy of PQ (0·25 mg/kg/day × 14 days) given concurrently with standard doses of either dihydroartemisinin–piperaquine (DP) or artemether–lumefantrine (AL). A relapse control arm received AL without PQ. The 384 enrolled subjects were followed for 180 days to assess efficacy against relapse, along with CYP2D6 genotyping, methaemoglobin monitoring, and measurement of PQ absorption and metabolism.ResultsBoth PQ treatment arms had significantly reduced rates of current P. vivax parasitamiea (PQ-AL: HR=0·50, CI95[0·33–0·75], PQ-DP: HR=0·34, CI95[0·22–0·52] P < 0·001) relative to no PQ. However, neither regimen provided adequate clinical efficacy (PQ-AL: 43·7%, PQ-DP: 34·1%). No significant differences were observed between PQ-AL and PQ-DP in CYP2D6 genotype-predicted activity scores, methaemoglobin levels, or concentrations of PQ and its metabolites (5,6-OQ and CPQ) on day 7 post-initation of dosing.ConclusionsThe dose of PQ administered in this study appears equally inadequate when used in combination with either DP or AL for radical cure. Higher PQ doses are required for effective radical cure in the Western Pacific, where PQ-tolerant Chesson-like strains still appear to commonly occur.Clinical trial registrationhttps://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=372150, identifier ANZCTR 12617000329369, Universal Trial Number (UTN) U1111-1191-4968.